1995
DOI: 10.3109/08916939508995700
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Thyroid Tissue from Patients with Hashimoto's Thyroiditis

Abstract: To clarify whether apoptosis of thyroid follicular epithelial cells occurs at the tissue level in autoimmune thyroiditis, 17 specimens of thyroid tissues with Hashimoto's thyroiditis were stained for fragmented DNA. Almost all nuclei of follicular epithelial cells forming atrophic thyroid follicles surrounded by mononuclear cell infiltration and fibrosis showed positive staining. With increasing distance from lymphoid cell follicles, the percentage of follicular epithelial cells with DNA fragmentation-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
6

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 10 publications
5
67
0
6
Order By: Relevance
“…Flow cytometric analysis showed more clearly that ceramide induced apoptotic cell death in FRTL-5 thyroid cells. Recently, several studies demonstrated that apoptosis was involved in cell death of normal thyrocyte and thyroid diseases such as goiter (Tamura et al, 1998) and thyroiditis (Kotani et al, 1995), and also suggested that the mechanisms by which thyroid cells undergo apoptosis were mediated by Fas/Fas ligand system (Arscott et al, 1997;Tamura et al, 1998). In consideration of several findings indicating that sphingomyelin pathway is involved in Fasmediated apoptotic signaling in various type of cells (Gulbins et al, 1995;Tepper et al, 1997;Boesen-de Cock et al, 1998), our results also suggested that ceramide may play a role in Fas-mediated apoptosis in thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis showed more clearly that ceramide induced apoptotic cell death in FRTL-5 thyroid cells. Recently, several studies demonstrated that apoptosis was involved in cell death of normal thyrocyte and thyroid diseases such as goiter (Tamura et al, 1998) and thyroiditis (Kotani et al, 1995), and also suggested that the mechanisms by which thyroid cells undergo apoptosis were mediated by Fas/Fas ligand system (Arscott et al, 1997;Tamura et al, 1998). In consideration of several findings indicating that sphingomyelin pathway is involved in Fasmediated apoptotic signaling in various type of cells (Gulbins et al, 1995;Tepper et al, 1997;Boesen-de Cock et al, 1998), our results also suggested that ceramide may play a role in Fas-mediated apoptosis in thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, no reports have been available about ceramide-induced apoptosis and effect of ceramide on PLD activity in thyroid cell. In thyroid cells, apoptosis is suspected of being involved in the regulation of normal glandular size and appears to be one of the major modes of thyrocyte death in autoimmune thyroid disease (Kotani et al, 1995;Tanimoto et al, 1995). With these premises, in the present study we have examined the effects of ceramide on apoptotic cell death and the possibility that PLD may be involved in apoptotic cell death in FRTL-5 thyroid cells.…”
Section: Introductionmentioning
confidence: 99%
“…HT is characterized primarily by destruction of thyroid tissue. Immunohistological investigation of HT tissue indicates that apoptosis might be a possible mechanism for cell death of thyrocytes (1,2), whereas reduced thyrocyte cell death was observed in the stimulated thyroids from GD patients (2).…”
Section: Introductionmentioning
confidence: 97%
“…Não há relatos na literatura sobre os índices apoptóticos em tiróides normais. Porém, sabe-se que a apoptose tem sido observada, ocasionalmente, em secções histológicas de tiróide normal (16), e este processo é anormalmente acelerado durante as fases de maior atividade da Tiroidite de Hashimoto (17).…”
Section: Discussionunclassified